Lectora Inspire Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Jane Cristi Faradilah Merinda Karno; Muhammad Turhan Yani; Raden Roro Nanik Setyowati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is development research, namely the development of learning media with Lectora Inspire to improve the critical thinking skills of class VI students. This type of research is research and development (R&D) using the 4D model, namely Define, Design, Develop and Disseminate. Researchers used a Pre-Experimental Design in the form of a One-shot Case Study. The subjects of this study were 37 students of class VI B at SDN Wonokusumo VI/45 Surabaya for the 2022/2023 academic year. Research produces learning media with a decent Lectora Inspire that meets the criteria of validity, practicality, and effectiveness. In the trial, the classical learning completeness was 91.89%.